A Haunted Landscape and Its Drained Souls: The Last Rush to Heritage and Archaeology in Turkey - Atakuman, Çiğdem (Journal of Mediterranean Archaeology, 2021)
Although the ultimate aim of the dominant heritage discourse and practice is to preserve culture in a way that contributes to peace and human prosperity, its paradoxical outcome has been to erase the variety of ways that people can relate to the past and to normalize ethnic and religious conflicts as well as globally deepening inequalities of class, race and gender. In this context, searching for civilization in the past has become an increasingly irrational activity, specifically in geopolitically important zones such as the Middle East and Turkey, where millions of immigrants, along with numerous minorities and economically impoverished populations, are currently denied access to the living standards of modern civilization. This paper aims to highlight these paradoxes inherent in the dominant heritage discourse and practice through the example of a recent heritage awareness-raising and capacity-building project, Safeguarding Archaeological Assets of Turkey (SARAT). Furthermore, based on two ethnographic case studies of treasure hunting from Turkey and Greece, it is also argued that the past is embodied in our questions of who we are and in our difficulties of belonging in today’s social landscape. Heritage, therefore, will continue to be in conflict and danger, unless people come to understand that they relate to the past in a variety of ways as regards the very core of the thick history of world politics.